PENYUSUNAN LAPORAN KEBERLANJUTAN BERDASARKAN PERATURAN OTORITAS JASA KEUANGAN NO. 51 TAHUN 2017 PADA PT. BPR SURYA ARTHA UTAMA PERSERODA SURABAYA - Nastiti, Kinanti; Bayangkara, I. B. Ketut (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
In order to make sure that PT. BPR Surya Artha Utama Perseroda Surabaya complies with Financial Services Authority (OJK) Regulation No. 51/POJK.03/2017, which is about sustainable finance, this study aims to evaluate how the company creates its sustainability reports. Data was gathered via in-depth interviews, document analysis, and direct observation; the research employs a qualitative approach, particularly a case study technique. The findings reveal that PT. BPR Surya Artha Utama has not fully integrated environmental sustainability reporting. There remains a gap in comprehensive mapping and reporting on environmental impacts such as waste management, energy use, and emission reduction efforts. These environmental aspects are crucial for comprehensive sustainability reporting as per GRI guidelines. In conclusion, PT. BPR Surya Artha Utama has shown significant progress in economic and social sustainability reporting in line with OJK Regulation No. 51/2017 and GRI guidelines. To achieve full compliance and enhance the quality of its sustainability reporting, the company needs to expand its reporting scope to include environmental aspects. These steps are essential to ensure that the resulting reports not only comply with regulations but also provide a clear and accurate portrayal of the company's overall sustainability performance.